Overview of Patient Safety Culture Among Nurses in Providing Services at Hospital - Karimah, Wasiatul; Porusia, Mitoriana (Jurnal Keperawatan Profesional (KEPO), 2025)
Nurses play a vital role in maintaining patient safety as they are at the frontline of healthcare services. Patient safety culture needs to be measured as an indicator of service quality. This study aimed to describe the patient safety culture among nurses at the Research Partner Hospital. This study was conducted at a Type C General Hospital located in Sukoharjo, using a descriptive quantitative method and a cross-sectional design. The sample consisted of 167 nurses selected through purposive sampling, with data collected via the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. The results showed that the patient safety culture was categorized as "medium" (55,28%), reflecting a fairly good understanding however, it requires for safe services to meet a high expectation. Strong dimensions included teamwork within units (80,08%) and organizational learning, continuous improvement (83,63%). However, weak areas included open communication (47,70%), staffing (19,16%), patient handoffs (47,15%), and non-punitive responses to errors (26,74%). Therefore, the hospital needs to improve these weak aspects through training, enhanced communication, and stronger management support.